Multigene barcoding and phylogeny of selected Engraulidae species. (3rd April 2019) - Gangan, Shardul S.; Pavan-Kumar, A.; K., Jaiswar A.
Abstract: Anchovies (Engraulidae) are one of the ecologically important groups and often difficult to identify due to their small size and overlapping morphological characters. In the present study, reference DNA barcodes were generated for 82 individuals representing 13 species of Engraulidae family using mitochondrial Cytochrome c oxidase subunit I ( COI ) and 16S rRNA genes. The average genetic distance value of COI gene for conspecific, congeneric and confamilial is 0.25, 20.45 and 22.28%, respectively. Mitochondrial 16S rRNA showed an average divergence value of 0.60, 10.28 and 14.37% for within species, between species and within families, respectively. Comparison of the present study reference barcodes with the reported sequences revealed high frequency of misidentification of species and possible occurrence of cryptic species in this family. Phylogenetic tree reconstructed using different methodologies revealed monophyletic nature of genus Stolephorus and the evolutionary relationship within genus Stolephorus is defined as ([ S. insularis: S. tamilensis ] S. dubiosus ( S. waitei [ S. commersonnii: S. indicus ])).